1993
DOI: 10.1111/j.1471-4159.1993.tb03544.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of GM1 Ganglioside Treatment on Glial Fibrillary Acidic Protein Content in the Rat Septum and Hippocampus After Partial Interruption of Their Connections

Abstract: The glial fibrillary acidic protein (GFAP) content was investigated using immunoblotting techniques in the septum and hippocampus of the rat after bilateral lateral fimbria transection. Seven days after surgery GFAP content increased significantly both in the septum (140% of control) and hippocampus (120% in dorsal, the less denervated, and 145% in the most denervated ventral part), indicating the occurrence of reactive gliosis. The GM1 treatment caused statistically significant attenuation of GFAP increment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Electrophoresis and immunoblotting were essentially performed according to Hozumi et al [19] as described in detail previously [36].…”
Section: Gfap Immunoblottingmentioning
confidence: 99%
“…Electrophoresis and immunoblotting were essentially performed according to Hozumi et al [19] as described in detail previously [36].…”
Section: Gfap Immunoblottingmentioning
confidence: 99%
“…Ganglioside shows potential therapeutic efficacy in brain injury induced by ischemic stroke or trauma (Leon et al, 1990;Merlo Pich et al, 1992). It is also reported that GM1 has a great effect on the suppression of gliosis in hippocampus (Oderfeld-Nowak et al, 1993;Jeglinski et al, 1996). Here we report that the combination of hUCMSC transplantation with GM1 administration promoted significantly better behavioral recovery following HIE than did cell transplantation alone.…”
Section: Discussionmentioning
confidence: 96%